Evaluation of selected fodder species for alley cropping systems - Louhaichi, Mounir; Hassan, Sawsan (Range Management Society of India, 2023)
This study examined various shrub species integrated into field crops (wheat, vetch, barley), including leguminous varieties (Medicago arborea, Colutea istria, Coronilla glauca), Atriplex species (A. canescens, A. nummularia, A. undulata), and Opuntia ficus-indica. It assessed their suitability based on forage production, quality, direct browsing, seasonal suitability for direct browsing and soil fertility. Atriplex species demonstrated higher suitability indexes. While leguminous species enhanced soil nutrient status, their low initial biomass productivity limited suitability for livestock forage. Opuntia ficus-indica, with a lower suitability index, was deemed unsuitable for direct browsing, as it was primarily a cut-and-carry crop. Therefore, the successful implementation of alley cropping systems requires a careful balance and analysis of shrub species that not only provide ample forage biomass support but also direct browsing and contribute to enhanced soil conditions for crop growth. This approach holds promise for sustainable and productive farming practices.